Cloud Computing and Offloading Framework - Najim, Ahmed Haitham; Guirguis, Shawkat k.; Madbouly, Magda mohammed (Discoveries in Agriculture and Food Sciences, 2014)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 12pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Information Technology (IT) field before cloud computing is not the same after. It has recently accelerated as new criteria for presenting and delivering services over the Internet. Cloud Computing is reacting positively as a concept that may greatly improve the smart devices (Smartphone, Tablet and Fablet) reliability. This paper mainly concentrates to enhance the smart devices dependability through and applications (app) during offloading of services among cloud and device to save energy, many challenges had faced that idea ex: unstable network, unstable Internet services, Synchronization and the limitations of open source smart devices operating system (OS). In order to cure the earlier challenges, An Android OS used with a new layer to offload the non-critical app’s jobs. That should occur in One’s of two clouds developed specially to do that, the first cloud is a private, connected with smart device through the same data network on-line and the second cloud is a public, related to the previous cloud and the smart device off-line when Internet exists. Using this system, Smart device users may choose to run their mobile application jobs either locally or offloading it to the cloud, this shall save energy spent from the smart device battery when using Third generation of mobile network (3G) or WI-FI. This system has achieved in the provision of high-energy reached 98.67% and will be seen in the context of this research paper.